DOI: 10.31274/rtd-180813-7334
|View full text |Cite
|
Sign up to set email alerts
|

The properties of starch with relation to time of formation of starch gels

Abstract: has been reproduced from the microfilm master. UMI films the text directly from the original or copy submitted. Thus, some thesis and dissertation copies are in typewriter face, while others may be from any type of computer printer. The quality of this reproduction is dependent upon the quality of the copy submitted. Broken or indistinct print, colored or poor quality illustrations and photographs, print bleedthrough, substandard margins, and improper alignment can adversely affect reproduction.In the unlikely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Establishing a standard for any of these characteristics was found to be difficult since iDiividuals vary so videly in their evaluation of quality. (3) found that vhen starch concentrations of one or two per cent were used, a discontinuous gel was formed and separate clumps of gel were visible. The amount of syneresis was affected by the concentration of starch used, the exposed surface area or the gel, the variety of starch used, certain added substances, and the age of the gel .…”
Section: Review Of Litmaturementioning
confidence: 98%
“…Establishing a standard for any of these characteristics was found to be difficult since iDiividuals vary so videly in their evaluation of quality. (3) found that vhen starch concentrations of one or two per cent were used, a discontinuous gel was formed and separate clumps of gel were visible. The amount of syneresis was affected by the concentration of starch used, the exposed surface area or the gel, the variety of starch used, certain added substances, and the age of the gel .…”
Section: Review Of Litmaturementioning
confidence: 98%